Illegal harvesting of Sparrow plant (Saposchnikovia divaricate (Turcz.) Schischk.) and its policy environment - Oyunbileg, Khaltar; Munkhzul, Oyunbileg; Sumjidmaa, Sainnemekh; Oyuntsetseg, Batlai (Mongolian Journal of Botany, 2024)
There are more than 1100 medicinal plant species registered in Mongolian flora, thirty percent of these species are commonly used. The Sparrow plant (Saposchnikovia divaricata (Turcz.) Schischk.), which is listed on the rare and vulnerable plant of Mongolia, but it has been in danger of being scarce and destroyed by overharvesting, sales, and exports in recent decades. The biological resource and distribution of the Sparrow plant are not fully studied nationwide, however quota of Sparrow’s harvesting is described by state within the legal framework every year based on previous studies in specific regions. Unfortunately, there is still lack of statistical data or information on amount of illegal harvesting and policy regulations related to the Sparrow plant and its trade in Mongolia. Therefore, we searched the information about Sparrow in databases of Mongolian courts’ electronic and the Ministry of Environment and Climate Change to gather and analyze. The 191 cases filed in the Electronic Court of Mongolia totally, out of 122 cases were handled by the Court of First Instance. Within these 122 cases, 56 cases of which were unauthorized harvesting, 35 of which were stored, 49 of which were transported, 31 of which were purchased, and 36 of which were illegally smuggled across borders. Consequently, total of 22 tons of Sparrow plants have been illegally prepared and caused 2.3 billion Mongolian tugriks (MNT) of environmental damage. We found that 0.8 billion US dollars (5.4 tons of roots) of environmental damage recorded in General Agency for Police and damage of 0.3 billion US dollars (2.5 tons of roots) of damage recorded in General Agency for Specialized Inspection within Environmental Statistical Database. Дэрэвгэр жиргэрүү ургамлын хууль бус ашиглалт, шийдвэрлэгдсэн байдал Хураангуй: Монгол оронд 1100 гаруй зүйлийн эмийн ургамал байдгийн 30 орчим хувь нь түгээмэл хэрэглэгддэг. Үүний нэг нь Дэрэвгэр жиргэрүү (Saposchnikovia divaricata (Turcz.) Schischk.) бөгөөд уг ургамал нь тус улсын ховор, эмзэг ургамлын жагсаалтад ордог. Гэвч сүүлийн жилүүдэд хэт их хэмжээгээр түүж бэлтгэх, хууль бусаар худалдаалах, экспортлох болсоноос нөөцийн хэмжээ багасч байна. Тухайн ургамлын биологийн нөөц Монгол орны хэмжээнд тодорхойгүй боловч тодорхой бүс нутгуудын хэмжээнд хийгдсэн судалгааны ажлуудад үндэслэн хуулийн хүрээнд түүж бэлтгэх хэмжээг жил бүр улсаас тогтоодог. Гэвч тухайн ургамлыг улсаас тогтоосон хэмжээнд болон хууль бусаар хир хэмжээнд түүж бэлтгэж байгаа талаар мэдээ баримт хомс байна. Иймд бид хуулийн хүрээнд шийдвэрлэгдсэн хэргүүдийг Монгол улсын шүүхийн цахим сан, Байгаль орчин, уур амьсгалын өөрчлөлтийн яамны цахим сангуудаас шүүж, тоон мэдээлэл цуглуулж, хэрхэн зохицуулагдаж байгаа талаар дүн шинжилгээ хийхийг зорьлоо. Бид Монгол улсын Шүүхийн шийдвэрийн цахим сангаас Дэрэвгэр жиргэрүүтэй холбоотой 191 хэрэг бүртгэгдсэнийг илрүүлсэн ба үүний 122 нь Эрүүгийн анхан шатны шүүхээр шийдвэрлэгдсэн байна. Үүнд: зөвшөөрөлгүйгээр түүж бэлтгэсэн 56, хадгалсан 35, тээвэрлэсэн 49, худалдан авсан 31, хилээр хууль бусаар нэвтрүүлсэн 36 хэрэг байна. Энд нийт 22 тонн Дэрэвгэр жиргэрүү ургамлын үндсийг хууль бусаар бэлтгэж, байгаль орчинд 2.3 тэрбум төгрөгийн хохирол учруулсан нь тогтоогдсон. Мөн Байгаль орчны статистикийн мэдээллийн санд ЦЕГ-т байгаль орчинд 0.8 тэрбум төгрөг (5.4 тонн үндэс), МХЕГ-т 0.3 тэрбум төгрөг (2.5 тонн үндэс)-ийн хохирол байгаль орчинд учруулжээ. Түлхүүр үг: Дэрэвгэр жиргэрүү, хууль бус ашиглалт, гэмт хэрэг